PELATIHAN TEKNIK ELEKTROPLATING NIKEL BAGI INDUSTRI KERAJINAN KUNINGAN DI DESA KAMASAN KABUPATEN KLUNGKUNG - Nindhia, T. G. Tirta; Surata, I W.; Atmika, I K. Adi; Negara, D.N.K. Putra; Komaladewi, A.A.I.A. Sri; Sucipta, I M. (Buletin Udayana Mengabdi, 2013)
The Village of Kamasan at Klungkung in the Province of Bali is recognized as a centre of metal handicrafts, especially the handicraft made from brass. Many home industries for the brass handicraft are established in this village. Recently due to Rapid progress of Tourism in Bali, The brass handicraft in Kamasan are growing well because the demand for the souvenir. However some problem arise such as limited of variation, and surface quality of the brass handicraft that tend to become blurred or dull due to the process of oxidation. This condition make the brass handicrafts become not so interest as silver handicrafts that can shine for quite long time. To overcome this problem it is needed to coating the surface of the brass handicrafts so that there will be no contact with oxygen. The coating will be more benefit if able to exhibit more interesting appearance, as what nickel coating can affect the appearance of the surface to become like silver but more clear. Equipment for nickel elektroplating was designed for this purpose and donated for this purpose. The unique of the equipment that was donated were small in size therefore only low electric power is needed, only 1 liter electrolyte was used and can be use many time. The positive result is obtained for this activity where all participants able to operate the elektroplating process with excellent result.